No Evidence of Reactivation of Hepatitis B Virus Among Patients Treated With Ledipasvir-Sofosbuvir for Hepatitis C Virus Infection - Sulkowski, Mark S. (Clin Infect Dis, 2016)
Postmarketing cases of hepatitis B virus (HBV) reactivation during hepatitis C treatment have been reported. We analyzed serum samples from patients in a clinical trial of ledipasvir-sofosbuvir in Taiwan and Korea. Of the 173 patients enrolled, 103 (60%) had been previously infected with HBV. None showed evidence of HBV reactivation.